ANALISIS BIBLIOMETRIK TREN PENELITIAN KEUANGAN SYARIAH DI INDONESIA TAHUN 2019-2023 - ANDRIANI SYOFYAN; GUSTI DIRGA ALFAKHRI PUTRA (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2025)
Islamic finance is one of the sectors currently focused on by the government for development. This commitment is reflected in the Islamic financial development initiatives outlined in the Indonesian Islamic Economic Masterplan 2019–2024. This literature study is positioned to map the development trajectory of research in the field of Islamic finance. Employing a qualitative approach, this study applies bibliometric analysis assisted by the VOSViewer software. Article data were sourced from national journals indexed in Google Scholar and retrieved via Publish or Perish. The search boundaries were focused on articles published periodically throughout the 2019–2023 period, with a maximum sample quota of the top 500 articles. The findings of this study provide insights into the evolving direction and focus of Islamic finance research, as well as identify potential future research avenues to advance the understanding of Islamic financial concepts. This research trend in Islamic finance has the potential to offer deeper insights into the field and highlight specific sectors that warrant further investigation.